Pemanfaatan Fasilitas Kredit Mikro Dalam Peningkatan Usaha Kecil dan Menengah (Studi kasus di BRI Unit Teling) - Reyma Shania lumintang; John Montolalu; Dantje Kelles (JURNAL ADMINISTRASI BISNIS, 2015)
ABSTRACT : Small industry and micro, in this time get attention a large enough , from various government, banking, correctional facility, and also institute Internasional, because provenproven small industry represent part of rescuer national economy after feel crisis economy that endless in Indonesia.One of the problems faced by micro and small entrepreneurs besides human resource is capital industry developing effort, and this time in concerned in enableness provision capital to small industry and micro in provision credit from banking.This research implemented at PT. Bank BRI (Persero) Unit Teling as one of the institute provide and give loan. Capital effort from entreprenur small and micro.Target research is to analyzing about exploiting facility credit micro in step up small industry and micro with method deskriptif and way of data collecting is run kounsioner and interview.As for research which be used in analysis data to exploiting facility credit micro is method Ordinary Least Square (OLS) with be used appliance analysis for manage data is with be ussed SPSS 15.0 For Windows.Based on the results research show that credit micro had an effort on positive to step up effort where describable in the right perspective relation indicator step up turnover result industry small and micro.Keywbords : Credit Facility, Small industry and micro